Penyaluran Dana Zakat di Badan Amil Zakat Nasional (BAZNAS) Kota Padang - Fajri Fitria; Widi Nopiardo (ZAWA: Management of Zakat and Waqf Journal, 2024)
The main problem in this research is what are the planning and budgeting procedures for distributing zakat funds at BAZNAS Padang City, what are the general provisions for distributing zakat funds at BAZNAS Padang City, what are the procedures for distributing zakat funds based on programs at BAZNAS Padang City and what are the supporting and inhibiting factors in the procedures distribution of zakat funds to BAZNAS Padang City. The type of research the author uses is field research, with qualitative descriptive methods. The data collection technique that the author used was interviews with BAZNAS Padang City and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The research results show that the first planning and budgeting procedures are carried out based on the RKAT which has been determined and approved by BAZNAS leadership to be distributed based on the budget allocation which is budgeted for BAZNAS programs in Padang City. Secondly, the general provisions for the distribution of zakat funds at BAZNAS Padang City are in accordance with the requirements that have been set to be fulfilled by prospective mustahik who will ask for assistance from BAZNAS Padang City according to the mustahik's needs. Thirdly, there are two procedures for distributing zakat funds based on the program, namely distribution using proposals and distribution on the amil's own initiative which distributes directly to the mustahik. And the fourth supporting factor is that the budget distributed is sufficient, establishing good cooperation with the government and being supported by competent amil-amil at BAZNAS Padang City. The inhibiting factor in distribution procedures is the community's low level of thinking, which hinders the distribution of aid to mustahik